Town Centricity Model – Delimiting the center of Athens, Greece - Ioannis Marakakis; Angelos Siolas; Thomas N. Chatzichristos (European Journal of Geography)
Town centres have been analysed by researchers according to the specific parameters of their studies such as concentration cores of economic activity or on the basis of their social and demographic attributes, diversity of land uses, etc. However, it is the synthesis of all centre’s characteristics that most completely define it. Moreover, in Greece, there is no sufficient statistical information available concerning town centres and it is necessary to create such data in order to improve their monitoring, control and planning. In order to apply this information, the boundary of town centre has to be set. This paper envisages in the definition of a town centre, the creation of a “Town Centricity Model” and the development and implementation of a consistent methodology resulting to its delimitation. After survey, analysis and evaluation of characteristics serving as centrality estimators, the most critical are deployed and the methodology is implemented. The latter concerns the design and creation of a geodatabase in a Geographic Information System (GIS) with features and attributes set to the spatial reference unit of a building block. The use of both vector and raster spatial analyses are addressed, the most representative qualitative methods are surveyed and weighting factors with the use of Delphi method are assigned. The pilot study of the aforementioned methodology is implemented in a case study area located in the municipality of Athens in Greece, resulting to the delimitation of its centre. The results are presented and ongoing future research is further discussed.